DETERMINAN RISK PERCEPTION DAN DUKUNGAN SOSIAL DENGAN STRATEGI KOPING PADA PENYINTAS HIV/AIDS - Indah, Fenita Purnama Sari; Pratiwi, Rita Dwi; Andriati, Riris; Ismaya, Nurwulan Adi; Aulia, Gina; Ayuningtyas, Gita; Romlah, Siti Novy (Edu Dharma Journal :Jurnal penelitian dan pengabdian masyarakat, 2023)
Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) are still global health problems. Indonesia is ranked 5th as the country most at risk of HIV/AIDS in Asia, so the HIV/AIDS epidemic is also a problem in Indonesia. The research objective was to identify the determinants of coping strategies in HIV/AIDS survivors. This research is an analytical research with a cross sectional research design, and a quantitative approach. The research subjects in the group were selected randomly. The sample in this study were PLHIV recorded at the Regional General Hospital (RSUD) of Tangerang Regency totaling 36 PLWHA. Risk perception and social support with Coping Strategies stated that there was no relationship between Risk perception and Coping Strategies in the Tangerang District Hospital. Further research is needed on other matters related to coping strategies and innovative steps that can be taken to improve coping strategies in PLWHA (People with HIV/AIDS).ABSTRAKHuman Immunodeficiency Virus (HIV) dan Acquired Immune Deficiency Syndrome (AIDS) sampai saat ini masih menjadi masalah kesehatan global. Indonesia berada pada urutan ke-5 sebagai negara yang paling berisiko HIV/AIDS di Asia, sehingga epidemi HIV/AIDS menjadi permasalahan pula di Indonesia. Tujuan penelitian adalah mengidentifikasi faktor determinan strategi koping pada penyintas HIV/AIDS. Penelitian ini merupakan penelitian analitik dengan desain penelitian cross sectional, dan pendekatan kuantitatif. Subyek penelitian pada kelompok dipilih secara random. Sampel dalam penelitian ini yakni ODHA yang terdata di Rumah Sakit Umum Daerah (RSUD) Kabupaten Tangerang berjumlah 36 ODHA. Hasil: Pada Risk perception dan dukungan sosial dengan Strategi Coping menyatakan bahwa tidak ada hubungan Risk perception dengan Strategi Coping di RSUD Kabupaten Tangerang. Diperlukan penelitian lebih lanjut mengenai hal-hal lain yang berhubungan dengan strategi coping dan langkah-langkah inovasi yang dapat dilakukan untuk meningkatkan strategi coping pada ODHA (Orang dengan HIV/AIDS).